Upaya Menumbuhkan Cinta dan Toleransi Melalui Integrasi Kearifan Lokal dalam Ekonomi Islam - Syaifudin, Ahmat Arif; Zulianto, Aris; Aufani, Lukman (Proceedings of Annual Conference for Muslim Scholars, 2025)
This study aims to analyze efforts to foster love and tolerance through the integration of local wisdom in Islamic economic practices within the BMT Bintang 9 Forum in Bojonegoro. Using a descriptive qualitative approach, the research explores the social, spiritual, and cultural values that shape collaboration among Islamic financial institutions at the community level. The results show that the BMT Bintang 9 Forum functions not only as a coordination platform but also as a space for spiritual development and institutional strengthening based on the values of ukhuwah (brotherhood), mahabbah (love), and tasamuh (tolerance). Local wisdom such as guyub rukun (harmony), tepo seliro (empathy), and gotong royong (mutual cooperation) is integrated with the principles of maqashid sharia to create social harmony and economic productivity. The forum strengthens social capital, professionalism, and inter-BMT networks. Theoretically, this study expands the concept of Islamic economics grounded in local culture and spirituality as an inclusive, just, and sustainable Islamic economic model